A Study to Assess the Accounting Undergraduate Internship Programme: A University of Botswana Students' Perspective - MBEKOMIZE , Christian John (Asian Journal of Empirical Research, 2013)
The purpose of this study was to examine accounting interns’ satisfaction levels with some internship organisational issues and to establish from students’ perspective, the benefits of industrial learning. The survey method was used to solicit interns’ views and a purposive sampling technique was employed to select the students to respond to the questionnaire. The results of this study suggest that respondents were extremely satisfied with internship organisational issues pertaining to host organisations but greatly displeased with the educators’ contribution. They, however, attached a high value to the overall internship experience. Less than 50% of respondents indicated that their attitude was impacted by the internship. This paper recommends that educators should show more commitment to the internship programme and forge solid links with the industry partners where all stakeholders could have the same understanding of the programme and agree on their respective responsibilities and on how best to utilize the interns for the greater benefits of all.